2000
DOI: 10.1177/019262330002800308
|View full text |Cite
|
Sign up to set email alerts
|

DNA Adducts: Endogenous and Induced

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(38 citation statements)
references
References 68 publications
1
36
0
1
Order By: Relevance
“…Endogenous adducts, oxidative DNA damage and indirect action It has been suggested that damage to DNA from endogenous exposures may be orders of magnitude greater than those from exogenous sources including exposure to tobacco smoke (Povey, 2000). This does not imply, however, that endogenous agents do not play a role in tobacco carcinogenesis, because tobacco exposures can directly and indirectly increase oxidative stress.…”
Section: Emerging Issues In Tobacco Carcinogenesis and Dna Adductsmentioning
confidence: 99%
“…Endogenous adducts, oxidative DNA damage and indirect action It has been suggested that damage to DNA from endogenous exposures may be orders of magnitude greater than those from exogenous sources including exposure to tobacco smoke (Povey, 2000). This does not imply, however, that endogenous agents do not play a role in tobacco carcinogenesis, because tobacco exposures can directly and indirectly increase oxidative stress.…”
Section: Emerging Issues In Tobacco Carcinogenesis and Dna Adductsmentioning
confidence: 99%
“…With the potent alkylating agent, ethyl methanesulfonate, doses of 100 and 50 mg/kg, which produce alkylation of sperm DNA at the level of about 2 ethylations per 10 5 nucleotides and 5 ethylations per 10 6 nucleotides, respectively 63 , did not produce mutations 64 . This DNA alteration is about the same level as endogenous modification of DNA 39,40,65,66 . U n e x c i s e d D N A a d d u c t s i n c r i t i c a l s i t e s i n transcriptionally active DNA become promutagenic only when the cell divides.…”
Section: Mutagenesismentioning
confidence: 84%
“…A critical issue is the level at which DNA adducts have biological significance. Mammalian DNA has a high level of spontaneous modification [37][38][39][40] , in the order of about 1 lesion per 10 6 bases. Thus, the abovementioned chemical adducts levels are 10 to 100-fold lower than the spontaneous level of alteration.…”
Section: Dna Binding and Repairmentioning
confidence: 99%
“…DNA adducts have been assessed and quantified in almost all human tissues, but the preferred samples of study are white blood cells due to their availability, and lung tissue because the lung is the point of entry for most carcinogenic environmental contaminants (26). DNA adducts are evaluated by three main methodological approaches, all characterized by their sensitivity, specificity, cost and instrumentation (19).…”
Section: Dna Adductsmentioning
confidence: 99%